Clinical and laboratory observation on immunoglobulin replacement therapy switching from an intravenous to a subcutaneous route in a Malaysian X-linked agammaglobulinemia patient - Ali, Adli; Abdul Wahab, Asrul; Abdul Latiff, Amir Hamzah; Ismail, Intan Hakimah; Mohd Zaki, Faizah; Borhanuddin, Boekhren Karyostyko; Mohd Noh, Lokman (Malaysian Medical Association, 2022)
We report a clinical and laboratory observation in a boy with X-linked agammaglobulinemia (XLA) who underwent an immunoglobulin replacement therapy (IRT) via the subcutaneous route (IGSC) seven years after his IRT via intravenous route (IGIV). He was free of invasive infections when on IGIV but not the troublesome coughs a week before the next infusion. A switch to a subcutaneous route resulted in significant improvement of symptoms with good weight gain. When on 2-weekly IGSC cycle, adjusting dose for weight resulted in an IgG trough level of > 600 mg/dl.